Bureaucratic Sociability, or the Missing Eighty Percent of Effectiveness: The Case of Diplomacy. Issue 1 (1st January 2023) - Kuus, Merje
ABSTRACT: This paper examines and theorises sociability–'the play-form of association'–in diplomatic settings. I highlight the workings of sociable interaction in diplomacy and I explain how we can better discern its broader role in bureaucratic processes. Empirically, I use virtual diplomacy during the COVID-19 pandemic to illustrate the difference that in-person sociability makes in diplomatic practice. The second half of the paper title references a comment by Michael Clauss, Germany's ambassador to the European Union. Asked about virtual diplomacy, Clauss said that Zoom diplomacy is '20% as effective' as the in-person kind. Conceptually, I use contemporary political geography and international relations as well as two thinkers of earlier decades–sociologists Georg Simmel and Erving Goffman–to theorise sociability. Methodologically, I advocate a more playful approach to sources in our study of professional practice. My objective is to prompt further study of sociability in bureaucratic settings.